REVISITING TRANSFORMATIVE ISLAM - Norma Fitria (Postgraduate State Islamic Institute (IAIN) Metro, 2022)
This article argues that currently the Indonesian Muslim community is experiencing degradation in understanding Islam not only as an an sich religion. Islam has not been a driving factor for social change in aspects of national and state life. This study uses content analysis and comparative methods. Researchers conduct a study of texts related to Transformative Islam and then study various social events related to Transformative Islam. The research findings show that Islamic teachings in Indonesia have not become values ​​and ethos that encourage social change, unity and civic life, and are factors that support progressivity in the life of the nation and state. The researcher recommends that Muslims revisit the idea of ​​Transformative Islam in order to re-mainstream Islam as liberation, criticism and at the same time social change.